An Analysis of Joči’s Debated Paternity and His Role in the Altan Uruġ Royal Lineage of Činggis Khan - Agatay O. (Золотоордынское обозрение)
Research objectives: This article discusses Joči’s military-political role and status in the Mongol Empire (Yeke Mongol Ulus), beginning in the early thirteenth century and within the intra-dynastic relations of Činggis Khan’s chief sons. In particular, the article seeks to answer questions about Joči’s birth. Discrepancies between the Secret History of the Mongols and other written sources cast doubt on whether Joči was even a legitimate son of Činggis Khan, let alone his eldest one. In addition, this article includes an analysis of Joči’s place within the family and the traditional legal system of the medieval Mongols based on the principles of majorat succession outlined in the Mongol Empire. It establishes evidence of his legitimacy within the Činggisid dynasty’s imperial lineage (altan uruġ) – a point of view supported by his military-political career, his pivotal role in the western campaigns, his leadership at the siege of Khwārazm, and the process of division of the ulus of Činggis Khan. Research materials: This article makes use of Russian, English, and Turkic (Kazakh, Tatar, etc.) translations of key primary sources including the Secret History of the Mongols and works of authors from the thirteenth to seventeenth centuries, including Al-Nasawī, Shіhāb al-Dīn al-Nuwayrī, ‘Alā’ al-Dīn ’Aṭā-Malik Juvāynī, Minhāj al-Dīn Jūzjānī, Zhao Hong, Peng Daya, John of Plano Carpini, William of Rubruck, Jamāl al-Qarshī, Rashīd al-Dīn, Ibn Faḍl Allāh al-ʿUmarī, Uluġbeg, Ötämiš Hājī, Lubsan Danzan, Abu’l-Ghāzī, and Saγang Sečen. New secondary works regarding Joči published by modern Kazakh, Russian, Tatar, American, French, Chinese, Korean and other scholars were also consulted. Results and novelty of the research: Taking into consideration certain economic and legal traits of the medieval Mongols, their traditional practices, military-political events, and longterm developments in the Mongol Empire’s history, descriptions of Joči being no more than a “Merkit bastard” are clearly not consistent. The persisting claims can be traced to doubts about Joči’s birth included in the Secret History of the Mongols, the first extensive written record of the medieval Mongols which had a great impact on the work of later historians, including modern scholars. Some researchers suspect this allegation may have been an indirect result of Möngke Khan inserting it into the Secret History. This article argues that the main motivation was Batu’s high military-political position and prestige in the Yeke Mongol Ulus. After Ögödei Khan’s death, sons and grandsons of Ögödei and Ča’adai made various attempts to erode Batu’s significant position in the altan uruġ by raising questions regarding his genealogical origin. This explains why doubts about Joči’s status in the imperial lineage appeared so widely following his death in an intra-dynastic propaganda struggle waged between the houses of Joči and Тolui and the opposing houses of Ča’adai and Ögödei’s sons. This conflict over the narrative was engendered by the struggle for supreme power in the Mongol Empire and the distribution of conquered lands and property.